CONCURRENT QUANTIFICATION OF TADALAFIL AND SILDENAFIL IN COMBINED TABLET FORMULATION USING RP-HPLC METHOD - Mayur S. Jain; Dr. Shailesh K. Koradia (Revista Electronica de Veterinaria, 2024)
The current work aims to establish a validated RP-HPLC method for estimating the combined dosage of sildenafil and tadalafil. Using ZORBAX C18 (250 × 4.6 mm, 5 µm)as a stationary phase and mobile phase, the medicines were separated The mobile phase consisted of acetate buffer pH 3.0 adjusted with acetic acid and methanol (10:90, v/v) at a flow rate of 0.7 mL/min., at 280 mm detection was carried out. Sildenafil’s Rt was 4.611 minutes, while Tadalafil’s was 3.744 minutes. Tadalafil and sildenafil had respective percentage drug contents of 98.63% when the commercial formulation was examined using the established approach. In the 50–150 PPM range for Tadalafil and 50–150 PPM range for Sildenafil, the approach was determined to be linear.. The results showed that the quantitation limit for sildenafil was 1.65 PPM and the detection limit for tadalafil was 5 PPM. For both medications, the accuracy and precision scores were found to be close to 100% w/w. Additionally, the approach was proven to be specific and robust. Tadalafil and sildenafil in combination dosage form were found to be linear, specific, sensitive, precise, accurate, and robust when analyzed using the proposed RP-HPLC technique.